How sleep can help maximize human potential: The role of leaders. Issue 10 (October 2021) - Teyhen, Deydre S.; Capaldi, Vincent F.; Drummond, Sean P.A.; Rhon, Daniel I.; Barrett, Amelia S.; Silvernail, Jason L.; Boland, David M.
Abstract: Objective: During multi-domain operations (MDO), soldiers need the physical supremacy, cognitive dominance, and emotional resilience to help defend and win our nation's wars. Optimal sleep has been shown to boost physical performance and cognitive processing. This manuscript will discuss how recent advances in sleep science strongly argue for the integration of sleep planning into military operations. Design: Review article. Methods: We reviewed the current understanding of how sleep affects Soldier readiness, how sleep and pain are interrelated, and unique challenges to obtaining adequate sleep in military training environments. We then address solutions that can be implemented by leaders and individuals to manage warfighter fatigue and optimize unit performance. Results: Since sleep is foundational to soldier health and readiness, improving warfighter fatigue management is a priority for leaders. Conclusion: To succeed in MDO, military personnel require physical supremacy, cognitive dominance, and emotional resilience to fight and win. Sleep science is a rapidly emerging field, and the clear implications for maximizing human performance argue strongly for more deliberate integration into military training and operations. Leaders that incorporate sleep and fatigue management into the planning and execution phases of operations will help facilitate mission priorities and prove a powerful force multiplier.